2010
DOI: 10.1016/j.yjmcc.2010.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Effect of troponin I Ser23/24 phosphorylation on Ca2+-sensitivity in human myocardium depends on the phosphorylation background

Abstract: Protein kinase A (PKA)-mediated phosphorylation of Ser23/24 of cardiac troponin I (cTnI) causes a reduction in Ca 2+ -sensitivity of force development. This study aimed to determine whether the PKA-induced modulation of the Ca 2+ -sensitivity is solely due to cTnI phosphorylation or depends on the phosphorylation status of other sarcomeric proteins. Endogenous troponin (cTn) complex in donor cardiomyocytes was partially exchanged (up to 66±1%) with recombinant unphosphorylated human cTn and in failing cells si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
68
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 62 publications
(85 citation statements)
references
References 45 publications
15
68
0
2
Order By: Relevance
“…Calcium overload is interpreted to be an important mechanism for development of hypothermiainduced cardiac dysfunction [36]. Increased cAMP is also known to mediate increased phosphorylation of cardiac troponin I (cTnI) at sites Ser23/24 causing decreased myofilament calcium sensitivity [15]. Han et al showed that such cTnI phosphorylation takes place due to hypothermia and rewarming and gives the expected reduction of calcium sensitivity and force of contraction [8].…”
Section: Discussionmentioning
confidence: 99%
“…Calcium overload is interpreted to be an important mechanism for development of hypothermiainduced cardiac dysfunction [36]. Increased cAMP is also known to mediate increased phosphorylation of cardiac troponin I (cTnI) at sites Ser23/24 causing decreased myofilament calcium sensitivity [15]. Han et al showed that such cTnI phosphorylation takes place due to hypothermia and rewarming and gives the expected reduction of calcium sensitivity and force of contraction [8].…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of sarcomeric protein phosphorylation [15][16][17][18][19][20] and force measurements on single cardiomyocytes 21 was performed as described previously.…”
Section: Protein Analysis and Isometric Force Measurementsmentioning
confidence: 99%
“…PKC activity and the expression of the Ca 2+ -dependent isoform PKC were found to be increased in the failing human heart [106,107]. A number of studies have reported that PKC also causes a reduction in Ca 2+ -sensitivity of force development in human myocardium [105,108,109] and decreased maximum myofibrillar Mg-ATPase [110], suggesting that this kinase may reduce contractility and enhance relaxation of human myocardium [104].…”
Section: Phosphorylation Of Troponin By Protein Kinase-cmentioning
confidence: 98%